Pregunta
upstudy study bank question image url

Solve for the variable in the following equaitons: \( 5 x-2 x+5=13+x \) \( \sqrt{6}-2(r+2)^{2}+5=-45 \)

Ask by Zimmerman Malone. in the United States
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x = 4 \) \( r = –2 + \sqrt{\frac{50 + \sqrt{6}}{2}} \)  or  \( r = –2 – \sqrt{\frac{50 + \sqrt{6}}{2}} \)

Solución

We are given two equations to solve. ──────────────────────── 1) Solve 5x – 2x + 5 = 13 + x Step 1. Combine like terms on the left side:   5x – 2x = 3x,   so the equation becomes:   3x + 5 = 13 + x Step 2. Get all x terms on one side by subtracting x from both sides:   3x – x + 5 = 13   2x + 5 = 13 Step 3. Isolate 2x by subtracting 5 from both sides:   2x = 13 – 5   2x = 8 Step 4. Divide both sides by 2:   x = 8/2   x = 4 ──────────────────────── 2) Solve √6 – 2(r + 2)² + 5 = –45 Step 1. Combine the constant terms √6 and 5:   √6 + 5 – 2(r + 2)² = –45 Step 2. Isolate the squared term by subtracting (√6 + 5) from both sides:   –2(r + 2)² = –45 – (√6 + 5)   –2(r + 2)² = –45 – √6 – 5   –2(r + 2)² = –50 – √6 Step 3. Divide both sides by –2 (remembering to flip the sign):   (r + 2)² = (50 + √6) / 2 Step 4. Take the square root of both sides, remembering the ±:   r + 2 = ± √[(50 + √6) / 2] Step 5. Solve for r by subtracting 2:   r = –2 ± √[(50 + √6) / 2] ──────────────────────── Final Answers: 1) x = 4 2) r = –2 + √[(50 + √6) / 2]  or  r = –2 – √[(50 + √6) / 2]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

Let's tackle these equations one by one! For the first equation, \( 5x - 2x + 5 = 13 + x \): 1. Combine like terms on the left side: \( 3x + 5 = 13 + x \). 2. Now, subtract \( x \) from both sides: \( 3x - x + 5 = 13 \). 3. This simplifies to \( 2x + 5 = 13 \). 4. Next, subtract 5 from both sides: \( 2x = 8 \). 5. Finally, divide by 2: \( x = 4 \). For the second equation, \( \sqrt{6} - 2(r + 2)^2 + 5 = -45 \): 1. Start by simplifying the equation: \( \sqrt{6} + 5 - 2(r + 2)^2 = -45 \). 2. Combine \( \sqrt{6} + 5 \) to find it equals \( -45 \) (which can be tricky, so watch for signs). 3. Rearranging gives us \( -2(r + 2)^2 = -45 - \sqrt{6} - 5 \). 4. Solving further, we find \( 2(r + 2)^2 = 50 + \sqrt{6} \), leading to \( (r + 2)^2 = 25 + \frac{\sqrt{6}}{2} \). 5. Finally, take the square root and solve for \( r \): \( r + 2 = \pm\sqrt{25 + \frac{\sqrt{6}}{2}} \), so \( r = -2 \pm \sqrt{25 + \frac{\sqrt{6}}{2}} \). And there you have it—both variables neatly solved!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad